Group Processes. - Levine, John M. (Frontiers of social psychology., 2012)
It is impossible to understand human behavior without understanding the critical role that groups play in people's lives. Most of us belong to a range of formal and informal groups, including families, work teams, and friendship cliques. These groups absorb a great deal of our time and energy and are instrumental in satisfying our most fundamental needs. In addition, they connect us to larger social aggregates (e.g., political parties, business organizations, religious denominations) that influence our lives in important ways. This volume provides a comprehensive overview of classic and contemp.